DNA PROFILING IN CRIMINAL INVESTIGATION IN INDIA: RIGHT TO FAIR TRAIL VIS -A-VIS RIGHT TO PRIVACY - Podder, Hillol Saha (International Journal of Research -GRANTHAALAYAH, 2025)
The advancement of forensic science has transformed the Indian criminal justice system, with DNA profiling emerging as one of the most powerful tools for ensuring accurate identification of offenders, exoneration of the innocent and effective administration of justice. However, the growing reliance on DNA evidence has raised critical constitutional questions concerning the right to privacy and the right to a fair trial. This paper explores the legal, ethical, and human rights dimensions of DNA profiling in criminal investigations in India, analyzing the tension between individual privacy and the collective pursuit of justice. It examines the statutory developments brought by the Bharatiya Nyaya Sanhita (BNS), 2023, Bharatiya Nagarik Suraksha Sanhita (BNSS), 2023, and Bharatiya Sakshya Adhiniyam (BSA), 2023, in relation to their counterparts the IPC, CrPC, and the Indian Evidence Act, 1872. Through an analytical study of judicial precedents, human rights frameworks, and legislative intent, this paper argues that while DNA profiling strengthens the right to a fair trial by enhancing evidentiary accuracy, its intrusive nature necessitates robust procedural safeguards to protect individual autonomy and dignity under Article 21 of the Constitution.